Nehemiah's Greatest Day - Penny Frank; Tony Morris (UK USA Lion Publishing, 1987)
Retells the Old Testament story in which God uses Nehemiah to rebuild the walls of Jerusalem after the Jews return from many years of captivity in Babylon.
Australia
Keywords: Theology: Miscellaneous (3GddGghJ(B: (3eJaQbGJs; Bible stories, English -- Nehemiah; Bible stories -- Old Testament